"How Do I Engage in My Class?"; EFL Teachers' and Tertiary Students' Perceptions during Online Speaking Class - Masriatus Sholikhah; Afi Ni’amah; Riris Nur Eriyanti (Jurnal Pendidikan Bahasa, 2022)
Incorporated with the positive and negative perceptions of Robbins' theory (2002) and the concept of students' engagement pioneered by J.A Fredericks (2004) and Gibbs (2010), this research concerned with the students' and the teachers' perceptions about the use of online learning platforms based on student engagement in speaking class and if the students can be actively involved in aspects of behavior, cognitive, and emotional during the learning process. Carried out with a descriptive qualitative approach, this research obtained the data from the first- and fourth-year student college students speaking one and speaking 3 in STKIP PGRI Jombang, UNWAHA, and IAIN Kudus. It administered questionnaires and interviews to both students and teachers. The result showed that students' behavioral engagement was eventually high. However, their cognitive and emotional engagement was not significantly positive in some aspects. Hence, it contributes to understanding the various aspects of web-based classes and the EFL student engagement in the virtual speaking class.